Assessment on awareness of ovarian cancer risk factors and attitudes towards screening among women in Balik Pulau, Penang - Wahab, Syakirah Bainun Abdul (Pusat Pengajian Sains Kesihatan, 2014)
Women’s awareness of ovarian cancer (OC) risks and their attitudes towards screening may influence screening uptake. A cross sectional, descriptive survey was carried out to assess the awareness on ovarian cancer risk factor and attitude towards screening. In total. 87 women at Balik Pulau, Penang completed questionnaires by purposive selection for women that fits the inclusion criteria. Data was statistically analyzed using the software package SPSS version 20. Statistical significance was considered at p-value <0.05. In all. 74.7% participants answer correctly for the risk factor of increasing age although 94.3% unaware on increased risk tall women. Majority, 71.3% had a low level of awareness and only 28.7% has a high level of awareness of ovarian cancer risk factors. Participants of 58.6% strongly agree that ‘If more women went for ovarian screening there would be fewer deaths from OC. However, there are 17.2% of participants strongly disagree with statement ’the older 1 get the more I think about the possibility of getting OC. There are 83.9% of participants having a moderate level of attitudes and 16.1% of participants have a good level of attitudes. There is no participant with low attitudes. There are association between age and level of awareness on OC risk factor (p=0.047). There are also having association between highest educational level and level of awareness on OC risk factors (p=0.039). For other socio-demographic data (ethnicity and monthly income), there are no association with level of awareness on OC risk factors. There are no association between socio-demographic data (age. ethnicity, highest educational level and monthly income) with level of attitude towards ovarian screening. There are also no association between awareness on OC risk factors and attitude towards ovarian screening (p=l .000). The results show a need for improved public understanding about OC risks and provide important information for health educationalists about initiatives needed for future awareness, prevention and screening programmes.